Fetomaternal outcome in pregnancy with diabetes mellitus - Vyas, Ayushi H.; Shah, Sapana R.; Deliwala, Kruti J.; Parikh, Purvi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: South Asian population has more prevalence of diabetes mellitus in pregnancy which can impact both mother and foetus and can also increase the risk of future diabetes. Methods: Seventy pregnant women hospitalised at SVP from August 2021 to May 2024 for diabetes mellitus during pregnancy were the subjects of the current ambisprective cohort research. Results: There were 45 women (64.28%) with gestational diabetes mellitus and 25 women (35.72%) with overt diabetes among the 70 women who were reported. The following complications were seen in the pregnant women in this study: 24 cases of polyhydramnios (34.28% of the total), 18 cases of macrosomia in the foetus (25.7%), 1 case of foetal cardiac abnormality (1.4%), and 40 cases of caesarean section (57.15% of the total). Conclusions: In order to attain positive fetomaternal outcomes, preventive medicine should prioritise the early screening and diagnosis of diabetes during pregnancy, as this condition has negative consequences on the mother and the unborn child.